Front-End Development in React: An Overview - Chen, Songtao; Thaduri, Upendar Rao; Ballamudi, Venkata Koteswara Rao (Engineering International, 2019)
In front-end development, the function that react.js plays is becoming increasingly important, providing developers with new options to create new applications. This article discusses how react.js assists in constructing user interfaces and the benefits it offers in building front-ends. According to the survey carried out by Web Technology Surveys, react.js is utilized by a significant percentage of all websites today. We will not exaggerate the situation if we declare that React.JS is used everywhere. When it comes to websites, new audiences have various interests. This article discusses critical aspects of the framework, including its advantages over competing frameworks, how it works, and its architecture.